Hydraulic fracturing and water in Colorado: can they coexist? - Carlson, Ken, author (Colorado State University. Libraries, 2013)
Colorado has a long history of water and energy development although these have largely happened independently. In the future, energy development will rely more on water and water development more on energy. Currently, the overlap between water and energy is manifested most prominently in the shale oil and gas industry and the use of hydraulic fracturing. Extraction of shale-derived oil and gas has increased significantly over the last five years due to advances in the drilling and stimulation processes including hydraulic fracturing. Unlike previous oil and gas booms in the state, water is a critical operating material for the extraction process and the industry is now in the position of competing for the scarce water resources with other water users. This presentation will discuss water usage for hydraulic fracturing, prospects for recycling the water and the issues that need additional research.
Presented at the Fall 2013 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Community, Energy Development and the Environment", September 10, 2013, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Seminar presented by Ken Carlson: Associate Professor in Civil and Environmental Engineering at Colorado State University; Over 20 years of experience in water treatment, wastewater handling and environmental engineering; Director of the Center for Energy Water Sustainability within the CSU Energy Institute; BS in chemical engineering from the University of Wisconsin; MS in Civil Engineering from Colorado State University; PhD in Environmental Engineering from the University of Colorado-Boulder.
PowerPoint presentation.
Presented with Stephen Goodwin.
Keywords: risk management; development; gas consumption; natural gas; source water; fracking; Colorado